Transitioning to independent living: Experiences of homeless young adults in rapid rehousing. (June 2022) - Gurdak, Kristen; Bond, Lynden; Padgett, Deborah; Petering, Robin
Abstract: Rapid rehousing (RRH) is an intervention that is being adopted nationally to assist adolescents and emerging adults who are homeless. RRH provides short-term rental assistance for independent scattered-site housing, in addition to an array of support services for approximately 12–24 months. The aim of this study is to explore the experiences of young adults (18–23 years old) who had previously been homeless and who were enrolled in RRH programs set in two urban Northeastern cities, and their subsequent preparedness for independent living. Our sample mostly consisted of non-Hispanic Black females, many of whom identified as LGBTQ. Semi-structured interviews ( n = 15) were conducted after participants had been in the program for nine months - three months prior to their initial program completion date. Thematic analysis revealed three themes: the importance of tangible support, communication among all parties: staff lead the way, and "I gotta start learning to do it on my own". These domains provided essential assistance for young people to attain their goals and through this process they learned skills to live independently and transition into adulthood. These findings suggest that rapid rehousing programs and service providers should focus on these domains to facilitate successful transition to independent living for this population. Highlights: Rapid rehousing is an intervention that assists young adults who are homeless to attain independent housing. Additional research is needed to understand RRH for this population and their needs to transitioning to independent housing. This study seeks to understand the experiences of young adults in an RRH program and identify their needs. Results revealed three themes: tangible support, communication, and "I gotta start learning to do it on my own". Findings suggest that RRH programs should focus on these domains to facilitate successful transition to independent housing.